18F-FDG PET/CT in immunocompetent patients with primary central nervous system lymphoma: Differentiation from glioblastoma and correlation with DWI. Issue 104 (July 2018) - Zhou, Weiyan; Wen, Jianbo; Hua, Fengchun; Xu, Weixingzi; Lu, Xiuhong; Yin, Bo; Geng, Daoying; Guan, Yihui
Highlights: We found that FDG PET/CT was effective for differentiating PCNSL from GBM. Both SUVmax and T/N ratio were reliable measures for differentiating PCNSL from GBM. FDG metabolism indices were inversely proportional to the rADCs of PCNSL lesions. Abstract: Objectives: 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) is useful for the detection of cancerous lesions, and FDG uptake is related to the apparent diffusion coefficient (ADC) derived from diffusion-weighted imaging (DWI) of extracranial tumors. The purpose of our study was to investigate the ability of FDG PET/CT in distinguishing primary central nervous system lymphoma (PCNSL) from glioblastoma multiforme (GBM) and to explore the relationship between 18 F-FDG uptake and the ADC in patients with PCNSL. Methods: We reviewed 92 patients (40 with PCNSL and 52 with GBM) who underwent FDG PET/CT scans at disease onset. The maximum standardized uptake value (SUVmax), tumor to normal contralateral cortex activity (T/N) ratio, SUVmean, metabolic tumor volume (MTV), and total lesion glycolysis (TLG) of tumor lesions were calculated. Receiver operating characteristic (ROC) curves were generated to determine the diagnostic performance for FDG PET-related parameters to differentiate PCNSL from GBM. Twenty-eight patients with PCNSL (with 34 lesions) also underwent diffusion-weighted imaging. Pearson's correlation analysis was used to assess the relation between SUV- and ADC-derived parameters. Results: The SUVmax, T/N ratio, SUVmean, and TLG values were significantly higher in PCNSL than in GBM. Comparative ROC analysis indicated that the SUVmax had a greater area under the curve (AUC) of 0.910 than the T/N ratio (0.905, P = .85), SUVmean (0.836, P = .0006), or TLG (0.641, P < 0.0001). The T/N ratio had the highest specificity (94.23%) for differentiating PCNSL from GBM, while the SUVmax had the most optimal sensitivity (92.31%). Further combined analysis of the indices did not significantly improve the AUC. Moderate inverse correlations between the SUVmax, SUVmean, TLG, and the ADC ratio (rADC) were found in PCNSLs (r = −0.526, P = .002; r = −0.504, P = .004; and r = −0.483, P = .006; respectively). Conclusions: The SUVmax and T/N ratio may be reliable measures for differentiating PCNSLs from GBMs. Additionally, FDG metabolism indices were inversely proportional to the rADCs of PCNSL lesions.